An orally active, small-molecule TNF inhibitor that disrupts the homotrimerization interface improves inflammatory arthritis in mice - Javaid, Nasir; Patra, Mahesh Chandra; Cho, Da Eun; Batool, Maria; Kim, Yoongeun; Choi, Gwang Muk; Kim, Moon Suk; Hahm, Dae Hyun; Choi, Sangdun (Science Signaling, 2022)
Excessive signaling by the proinflammatory cytokine TNF is involved in several autoimmune diseases, including rheumatoid arthritis (RA). However, unlike the approved biologics currently used to treat this and other conditions, commercially available small-molecule inhibitors of TNF trimerization are cytotoxic or exhibit low potency. Here, we report a TNF-inhibitory molecule (TIM) that reduced TNF signaling in vitro and was an effective treatment in a mouse model of RA. The initial lead compound, TIM1, attenuated TNF-induced apoptosis of human and mouse cells by delaying the induction of proinflammatory NF-κB and MAPK signaling and caspase 3– and caspase 8–dependent apoptosis. TIM1 inhibited the secretion of the proinflammatory cytokines IL-6 and IL-8 by disrupting TNF homotrimerization, thereby preventing its association with the TNF receptor. In a mouse model of collagen-induced polyarthritis, the more potent TIM1 analog TIM1c was orally bioavailable and reduced paw swelling, histological indicators of knee joint pathology, inflammatory infiltration of the joint, and the overall arthritis index. Orally delivered TIM1c showed immunological effects similar to those elicited by intraperitoneal injection of the FDA-approved TNF receptor decoy etanercept. Thus, TIM1c is a promising lead compound for the development of small-molecule therapies for the treatment of RA and other TNF-dependent systemic inflammation disorders.
Keywords: Animals; Arthritis, Experimental; Arthritis, Rheumatoid; Cytokines; Disease Models, Animal; Humans; Mice; NF-kappa B; Receptors, Tumor Necrosis Factor; Tumor Necrosis Factor Inhibitors